2023
DOI: 10.3390/ma17010061
|View full text |Cite
|
Sign up to set email alerts
|

Numerical, Theoretical, and Experimental Analysis of LVL-CFRP Sandwich Structure

Michał Marcin Bakalarz,
Paweł Grzegorz Kossakowski

Abstract: Optimization of structural elements via composition of different components is a significant scientific and practical point-of-view problem aimed at obtaining more economical and environmentally friendly solutions. This paper presents the results of a static work analysis of small-size laminated veneer lumber (LVL) beams reinforced by a Carbon Fiber Reinforced Polymer (CFRP) sheet. The nominal dimensions of LVL beams were 45 × 45 × 850 mm, and 0.333- and 0.666-mm thick reinforcement layers were used. The reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Curves plotted with the red color were obtained from numerical analysis; curves plotted with the black color were from experimental tests. The obtained results are within the expected deviation when compared to the similar research regarding strengthening timber elements with FRP materials; for example, a 10% relative error was obtained when applying such a model for an LVL CFRP sandwich structure [43]. It should be pointed out that after the initial phase, due to the degradation of bending stiffness, the non-linear behavior of real-life elements occurs faster than in the simulation.…”
Section: Numerical Analysissupporting
confidence: 81%
See 4 more Smart Citations
“…Curves plotted with the red color were obtained from numerical analysis; curves plotted with the black color were from experimental tests. The obtained results are within the expected deviation when compared to the similar research regarding strengthening timber elements with FRP materials; for example, a 10% relative error was obtained when applying such a model for an LVL CFRP sandwich structure [43]. It should be pointed out that after the initial phase, due to the degradation of bending stiffness, the non-linear behavior of real-life elements occurs faster than in the simulation.…”
Section: Numerical Analysissupporting
confidence: 81%
“…Raftery et al [10] concluded a 10% enhancement of stiffness for timber beams strengthened with basalt rods with a 1.4% reinforcement ratio. From the point of view of the location of reinforcement, the most effective solution is the configuration wherein the reinforcement is placed on an external compressed and tensile face of the beam [43]; the average increases were 86% and 182% for one and two layers of CFRP, respectively. A slightly less effective solution is positioning the reinforcement on the sides of the beam.…”
Section: Bending Stiffnessmentioning
confidence: 99%
See 3 more Smart Citations